2021
DOI: 10.21037/apm-21-2466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dialectical behavior group therapy on the anxiety and depression of medical students under the normalization of epidemic prevention and control for the COVID-19 epidemic: a randomized study

Abstract: Background: During the epidemic, the mental health of college students was generally poor, especially anxiety and depression, which should be treated using counseling and intervention. This study aimed to observe the influence of dialectical behavior therapy on the anxiety and depression of medical students during the normalization of the prevention and control of the COVID-19 epidemic.Methods: A total of 26 medical students (experimental group) were treated with dialectical behavior therapy intervention for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The eight studies included a total of 1403 participants. Three main clusters of digital interventions administered to study participants were identified: CBT-/DBT-based interventions 33,34 ; mindfulness-based interventions 32,35,36 ; other types of interventions, i.e., positive psychology interventions (PPIs) 30,31 and mind-body interventions. 29 Control conditions mostly consisted of wait-lists and behavioural/psychoeducational interventions.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The eight studies included a total of 1403 participants. Three main clusters of digital interventions administered to study participants were identified: CBT-/DBT-based interventions 33,34 ; mindfulness-based interventions 32,35,36 ; other types of interventions, i.e., positive psychology interventions (PPIs) 30,31 and mind-body interventions. 29 Control conditions mostly consisted of wait-lists and behavioural/psychoeducational interventions.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Cognitive behavioral therapy, which aims to change individual thoughts and behaviors, has been the most widely used treatment method for depression thus far[ 106 - 110 , 113 - 115 ]. Mindfulness intervention programs[ 111 ] based on cognitive behavioral therapy and dialectal behavior group therapy[ 112 ] can effectively alleviate the depressive symptoms of college students.…”
Section: Nonpharmaceutical Prevention Of Depressionmentioning
confidence: 99%
“…Cognitive behavioral therapy offered to the students is also a proven way to decrease their anxiety level and modify their emotions and behaviors amid such emergencies. [ 29 ] It also could have contributed positively in our case as cognitive behavioral therapy was available at both the local university level through the counseling unit and at the public level through specialized COVID-19 clinics.…”
Section: Discussionmentioning
confidence: 96%